“ANKER” Video Prosedur K3 untuk Meningkatkan Kesadaran Kerja di Laboratorium Mikrobiologi - Putra, Renardi Erwinsyah; Hofifah, Siti Nur; Maemunah, Iin; Purwanti, Sri Tri; Barmana, Doni (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
This research aims to examine the production of occupational health safety (OHS) videos in microbiology laboratories. The procedure used is